Can holistic school readiness evaluations predict academic achievement and special educational needs status? Evidence from the Early Years Foundation Stage Profile. (February 2022) - Atkinson, A.L.; Hill, L.J.B.; Pettinger, K.J.; Wright, J.; Hart, A.R.; Dickerson, J.; Mon-Williams, M.
Abstract: This study examined the predictive validity of holistic school readiness evaluations using the 'good level of development' outcome from the Early Years Foundation Stage Profile (EYFSP). The EYFSP assesses a range of abilities at school entry including academic, language, socio-emotional, and motor skills. In particular, we examined whether the assessment predicted reading, writing, maths, and science ability two years later and future special educational needs (SEN) status ( N = 3739–5768). Children who reached a good level of development had higher odds of performing at expected (vs. below expected) levels on later academic assessments. This was particularly true for children with SEN. Reaching a good level of development also increased the odds of performing at above expected (vs. expected) levels on the academic assessments and lowered the odds of requiring SEN support. This demonstrates that holistic school readiness evaluations are powerful tools that can identify 'at risk' children. Highlights: Predictive validity of holistic school readiness evaluation assessed. Assessment predicted educational attainment two years later. Being 'school ready' critical for children with special educational needs. Evaluation can also predict special educational needs status.